65.1k views
5 votes
Use substitution to solve each system of equations. y = 4x + 22 4x – 6y = –32

(–5, 2)

(2, –5)

(–8, 1)

(4, 7)

User Naeio
by
5.4k points

2 Answers

7 votes

Answer:

(-5, 2)

Explanation:

We have the equations:


y=4x+22 and
4x-6y=-32

Using the substitution method, with y = 4x + 22 and replace it in the equation 4x - 6y = -32

4x - 6(4x + 22) = -32

4x -24x -132 = -32

-20x = -32 + 132

x = 100/-20= -5

Substituting the value of x in the first equations of the systems to clear x.

y = 4x + 22

y = 4(-5) + 22

y= -20 + 22 = 2

User Kin Siang
by
4.5k points
7 votes

Answer:

The answer is (-5,2)

Explanation:

So we have 2 equations and we need to solve them by substitution.

1) y = 4x + 22

2) 4x – 6y = –32

Since we already have y isolated in equation #1, we'll use that value in equation #2:

4x - 6(4x + 22) = -32

4x - 24x - 132 = -32

-20x = 100

x = -5

Then we put that value of x in the first equation:

y = 4 (-5) + 22 = -20 + 22 = 2

The answer is then (-5,2)

User Simon Guest
by
4.5k points